Salicylic acid and acibenzolar-S-methyl induce disease resistance to banana leaf spot caused by Curvularia eragrostidis - Bussabong, Noplapat; Tongsri, Veeranee; Songkumarn, Pattavipha (Agriculture and Natural Resources, 2021)
Leaf spot is a harmful disease that reduces the quantity and quality of banana yields in Thailand. This research aimed to investigate the molecular identity of a pathogen causing banana leaf spot, the effect of salicylic acid (SA; 0, 0.5, 1 and 1.5 mM) and acibenzolar-S-methyl (ASM; 0, 1, 2, 3, 4 and 5 mM) on pathogen growth in vitro, the reduction of disease severity and the induction of disease resistance in host plants. The virulent fungal pathogen was identified as Curvularia eragrostidis. Treatments of SA at 1.5 mM and ASM at all tested concentrations significantly inhibited the mycelial growth of the pathogen. Additionally, all concentrations of both activators significantly reduced disease severity by up to 77.8% for SA and 100% for ASM. Banana plants treated with 0.5 mM SA produced an early response of activating total phenolic compounds (TPCs) within 24 hr after inoculation (hai) and extremely stimulated the activity of peroxidase (POX) at 96 hai. In the 1 mM ASM treatment, the highest accumulations of endogenous SA and TPCs occurred at 24 and 96 hai, respectively. Plants treated with ASM also had the highest phenylalanine ammonia-lyase (PAL) and β-1,3-glucanase (GLU) activity levels at 96 hai. The activity of POX in the ASM treatment slightly increased at 24 hai. These findings revealed that the reduction of leaf spot disease in bananas occurred through the involvement of both activators in the direct suppression of the pathogen and the induction of disease resistance against C. eragrostidis. online